2022
DOI: 10.3390/molecules27041276
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Topical Forms of Polydeoxyribonucleotide, Vitamin C, and Niacinamide Attenuated Skin Pigmentation and Increased Skin Elasticity by Modulating Nuclear Factor Erythroid 2-like 2

Abstract: It is well-known that increased oxidative stress caused by ultraviolet B (UV-B) radiation induces melanogenesis and activates metalloproteinases (MMPs), which degrade collagen and elastin fibers, leading to decreased skin elasticity. Various antioxidant agents, such as vitamin C and niacinamide, have been evaluated for use as treatments for photoaging or skin pigmentation. In this study, we evaluated the ability of a topical liquid formula of polydeoxyribonucleotide (PDRN), vitamin C, and niacinamide (PVN) del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Subsequently, it was developed using a chemiluminescence detection solution (GE Healthcare, IL, USA) to visualize the proteins on the membrane. Western blot images obtained through visualization were analysed using the Image J software (NIH, DC, USA) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, it was developed using a chemiluminescence detection solution (GE Healthcare, IL, USA) to visualize the proteins on the membrane. Western blot images obtained through visualization were analysed using the Image J software (NIH, DC, USA) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…6 This may lead to vascular instability and the release of inflammatory cytokines and reactive oxygen species (ROS). 25,26 Our findings demonstrated that most clinicians perceived PN use as effective in vascular stabilization and anti-inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…The precise pathogenesis of erythema in inflammatory facial dermatosis is unknown, but one proposed etiology is that repeated episodes of microcapillary dilation result in loss of vascular tone and subsequent permanent microcapillary dilatation 6 . This may lead to vascular instability and the release of inflammatory cytokines and reactive oxygen species (ROS) 25,26 . Our findings demonstrated that most clinicians perceived PN use as effective in vascular stabilization and anti‐inflammation.…”
Section: Discussionmentioning
confidence: 82%
“…Then, the NVP-mix solution was filtered through a 0.2 μm filter (S2GPU11RE, Merck, CA, USA) to remove bacteria. A total of 1 mM of NVP-mix liquid contains 0.55 mM of niacinamide, 0.25 mM of vitamin C, and 0.18 mM of PDRN [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…PDRN causes the downregulation of tyrosinase, TYRP1, and MITF and shows an anti-melanogenesis effect [ 44 ]. Previously, our group reported that a mixture of nicotinamide, vitamin C, and PDRN decreased destruction of collagen and elastin fiber by decreasing metalloproteinases via modulating nuclear factor erythroid 2-like 2 and heme oxygenase-1 which reduced expression of NADPH oxidase [ 45 ].…”
Section: Introductionmentioning
confidence: 99%